PENGARUH METODE KOAGULASI, SEDIMENTASI DAN VARIASI FILTRASI TERHADAP PENURUNAN KADAR TSS, COD DAN WARNA PADA LIMBAH CAIR BATIK - Rahmah, Rahmah; Mulasari, Surahma Asti (Universitas Ahmad Dahlan, 2015)
Batik industry in Indonesia increased, so that the impact result from the production process in the form of wastewater is increasing. Wastewater disposal after staining and washing process without processing will improve environmental contamination such as TSS, COD and color levels. The problems of batik wastewater contamination can be resolved by treatment of wastewater in chemistry and physics. One way batik wastewater treatment are coagulation, sedimentation and filtration. Filtration media are used as filter media is activated charcoal, quartz sand and zeolite. The purpose of this research to determine the effect of coagulation, sedimentation and filtration variation method to decreased levels of TSS, COD and color in the wastewater of batik. The type of this research was a true experiment with pre-test post-test group design. Samples of this research were batik wastewater with levels of TSS, COD and color are 818 mg/ l, 1133,57 mg/ l and 100 TCU. Data analyzed using one-way ANOVA. The result after treatment of coagulation, sedimentation and filtration variety occurs decreased levels of TSS, COD and color on filtration variation of activated charcoal and quartz sand, respectively for 99,8%, 99,49% and 99,6%, variation of the zeolite filtration and activated charcoal was, 99,6%, 92,31% and 99,5%, and variations in zeolite filtration and quartz sand was 99,7%, 89,92% and 99,3%. Based on the statistical test using ANOVA test on the TSS levels were obtained p= 0,190, while the COD were obtained value of p= 0,008 and the value of color was p= 0,017. The methods of coagulation, sedimentation and filtration variation using activated charcoal, quartz sand and zeolite can reduce TSS, COD and color levels. There is no difference between the variation of filtration to decrease levels of TSS, while there is a difference between the variation filtration to decreased levels of effluent COD and color Batik.